Motivasi Mahasiswa Bergabung di Organisasi Intra Kampus (Studi Eksplorasi Mahasiswa Fakultas Ekonomika dan Bisnis Undip) - Firdausz, Rizky (Faculty of Economics and Business Diponegoro University, 2013)
This research was conducted in the Faculty of Economics and Business, DiponegoroUniversity. The objective is to find out and analyze the students motivations to join the intra- campus organization. Moreover, this study also aims to discover and analyze the perception of students related to student organization as a means of softskill development.Participants of research were choosed by using purposive sampling method and five students were active in student organization and five students were not active in studentorganization. This study used qualitative methods in data collection and analysis.The result of this study stated that according to the five intrinsic motivation factors consisting of goal, talent, intelligence, perspective, and interest, that perspective factor become the fundamental factor to influence student in order to join the intra-campus organization. Whereas, extrinsic motivation factors are consist of family, school, and society, school is the fundamental factors which influence student in order to join the intra-campus organization